The Western Wall : the dispute over Israel's holiest Jewish site, 1967-2000 - Cohen-Hattab, Kobi; Bar, Doron, 1965- (Jewish identities in a changing world, 2020)
"The Western Wall, Judaism's holiest site, occupies a prominent position in contemporary Jewish and Israeli discourse, current events, and local politics. In The Western Wall: The Dispute over Israel's Holiest Jewish Site, 1967-2000, Kobi Cohen-Hattab and Doron Bar offer a detailed exploration of the Western Wall plaza's evolution in the late twentieth century. The examination covers the role of archaeology in defining the space, the Western Wall's transformation as an Israeli and Jewish symbol, and the movement to open it to a variety of Jewish denominations. The book studies the central processes and shifts that took place at the Western Wall during the three decades that followed the Six-Day War-a relatively short yet crucial chapter in Jerusalem's extensive history"--